The PHD1 oxygen sensor in health and disease. (5th March 2018) - Kennel, Kilian B.; Burmeister, Julius; Schneider, Martin; Taylor, Cormac T.
Abstract: The hypoxia‐inducible factor (HIF) co‐ordinates the adaptive transcriptional response to hypoxia in metazoan cells. The hypoxic sensitivity of HIF is conferred by a family of oxygen‐sensing enzymes termed HIF hydroxylases. This family consists of three prolyl hydroxylases (PHD1–3) and a single asparagine hydroxylase termed factor inhibiting HIF (FIH). It has recently become clear that HIF hydroxylases are functionally non‐redundant and have discrete but overlapping physiological roles. Furthermore, altered abundance or activity of these enzymes is associated with a number of pathologies. Pharmacological HIF‐hydroxylase inhibitors have recently proven to be both tolerated and therapeutically effective in patients. In this review, we focus on the physiology, pathophysiology and therapeutic potential of the PHD1 isoform, which has recently been implicated in diseases including inflammatory bowel disease, ischaemia and cancer. Abstract : PHD1 expression and activity are under the control of a range of stimuli including molecular oxygen, metabolites, microRNAs and post‐translational modifications (PTMs). PHD1, through hydroxylation, regulates the activity of pathways including the hypoxia inducible factor (HIF) and nuclear factor‐κB (NF‐κB), which in turn regulate processes including inflammation, ischaemia and tumour growth.